PENGANGKATAN ANAK DAN AKIBAT HUKUMNYA TERHADAP HARTA BENDA PERKAWINAN ORANGTUA ANGKAT (STUDI PADA MASYARAKAT TIONGHOA DI KECAMATAN SENAPELAN KOTA PEKANBARU) - KHUSDJONO KHUSDJONO (PREMISE LAW JURNAL, 2015)
Adopting a child is intended not only to be the next generation but also to be the happy moment for the adoptive parents. In the Chinese ethnic group, especially those who live in Senapelan Subdistrict, Pekanbaru, adopting a child is recommended as a provocation so that the adopted child will become their offspring. The research used judicial normative method. The reason for adopting a child in the Chinese ethnic group in Senapelan Subdistrict, Pekanbaru was because they did not have any children, they did it as the provocation for getting a child, they felt pity on the child, and they needed the adopted child as their offspring. The procedure of adopting a child in the Chinese ethnic group in Indonesia is by the agreement between the adopted child’s parents and the future adoptive parents. After the agreement is settled, the ceremony is held by announcing the adoption to the public which states that there is an agreement between the adopted child’s parents and the future adoptive parents about the adoption. Keywords: Adopting a Child, Chinese Ethnic Group, Adoptive Parents’ Property